High-resolution comparative analysis of great ape genomes - Kronenberg, Zev N.; Fiddes, Ian T.; Gordon, David; Murali, Shwetha; Cantsilieris, Stuart; Meyerson, Olivia S.; Underwood, Jason G.; Nelson, Bradley J.; Chaisson, Mark J. P.; Dougherty, Max L.; Munson, Katherine M.; Hastie, Alex R.; et al. (Science (American Association for the Advancement of Science), 2018)
Most nonhuman primate genomes generated to date have been “humanized” owing to their many gaps and the reliance on guidance by the reference human genome. To remove this humanizing effect, Kronenberg et al. generated and assembled long-read genomes of a chimpanzee, an orangutan, and two humans and compared them with a previously generated gorilla genome. This analysis recognized genomic structural variation specific to humans and particular ape lineages. Comparisons between human and chimpanzee cerebral organoids showed down-regulation of the expression of specific genes in humans, relative to chimpanzees, related to noncoding variation identified in this analysis. Science , this issue p. eaar6343 Analysis of long-read great ape and human genomes identifies human-specific changes affecting brain gene expression. Genetic studies of human evolution require high-quality contiguous ape genome assemblies that are not guided by the human reference. We coupled long-read sequence assembly and full-length complementary DNA sequencing with a multiplatform scaffolding approach to produce ab initio chimpanzee and orangutan genome assemblies. By comparing these with two long-read de novo human genome assemblies and a gorilla genome assembly, we characterized lineage-specific and shared great ape genetic variation ranging from single– to mega–base pair–sized variants. We identified ~17,000 fixed human-specific structural variants identifying genic and putative regulatory changes that have emerged in humans since divergence from nonhuman apes. Interestingly, these variants are enriched near genes that are down-regulated in human compared to chimpanzee cerebral organoids, particularly in cells analogous to radial glial neural progenitors.